2018
DOI: 10.9734/jabb/2018/42855
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Microorganisms Associated with Automated Teller Machines in Calabar Metropolis

Abstract: The metallic keyboards of automated teller machines situated within Calabar metropolis were investigated for microbial contamination due to their vast dermal contact by multiple users. Swab sticks soaked with normal sterile saline were used to collect specimens from the keypads. Isolation was done on nutrient agar and eosine methylene blue (EMB) for bacteria and Sabouraud dextrose agar for fungi using standard microbiological procedures. Identification of microorganisms was done using colonial, microscopic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The statistical significant relationship between the bacterial isolates and the respective locations could be as a result of several factors such as, poor hygiene practices by ATM users, rainfall, wind and high concentration of users at ATM galleries. Similarly, [2] reported that the keypads of ATMs harbored more bacteria than the computer keypads and this may be due to the fact that, they are exposed to many users, environmental factors such as rain and climatic factors such as wind. The result of this study is also similar with the results of bacterial contamination from obtained the surfaces of the metallic keypads of the ATMs located within Abakaliki metropolis [6].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The statistical significant relationship between the bacterial isolates and the respective locations could be as a result of several factors such as, poor hygiene practices by ATM users, rainfall, wind and high concentration of users at ATM galleries. Similarly, [2] reported that the keypads of ATMs harbored more bacteria than the computer keypads and this may be due to the fact that, they are exposed to many users, environmental factors such as rain and climatic factors such as wind. The result of this study is also similar with the results of bacterial contamination from obtained the surfaces of the metallic keypads of the ATMs located within Abakaliki metropolis [6].…”
Section: Discussionmentioning
confidence: 98%
“…The method described by [2] was used. The swab sticks bearing the samples from each location were dipped into a test tube containing a sterile normal saline and was agitated for 5minutes before inoculums were collected from there and cultured by spread plate technique on manitol salt agar, eosin methylene blue agar, macConkey agar and salmonella shigella agar.…”
Section: Isolation and Identification Of Bacteriamentioning
confidence: 99%
“…Because of the incessant utilization of cell phones, the heat produced by the telephone makes a perfect temperature that underpins the development of microbes. The chance of getting contamination because of cell phones is high as they as kept in nearness or contact with our face, hands, and mouth giving a course to microbes to enter the body [16].…”
Section: Microbes Present On Cell Phonementioning
confidence: 99%
“…The extensive use of electronic devices such as ATMs is not excluded as a source of bacterial contamination (Saroja et al, 2013). Since microorganisms are ubiquitous, their presence on keypads/buttons of ATMs are inevitable and has been reported by various researchers (Stephen and Kwaku, 2011;Iquo et al, 2015;Agu et al, 2018;Aquino et al, 2019), and the tendency of these microorganisms to be picked by humans and get infected through oral, nasal or eyes contacts with contaminated fingers are very high (Stanley and Kayode, 2014;Aquino et al, 2019). This tendency increases with increase in human population as well as progressive digitization of banking systems abandoning the traditional system (i.e.…”
Section: Bajopas Volume 13 Number 1 June 2020mentioning
confidence: 99%